Atomically Flat, 2D Edge‐Directed Self‐Assembly of Block Copolymers (Adv. Mater. 3/2023). Issue 3 (19th January 2023) - Kim, Jang Hwan; Jeong, Hyeon U; Yeom, Hye‐In; Han, Kyu Hyo; Yang, Geon Gug; Choi, Hee jae; Kim, Jong Min; Park, Sang‐Hee Ko; Jin, Hyeong Min; Kim, Jaeup U.; Kim, Sang Ouk
Abstract : Self‐Assembled Nanodomains In article number 2207338, Jang Hwan Kim, Hyeong Min Jin, Jaeup U. Kim, Sang Ouk Kim, and co‐workers demonstrate the realization of sub‐10‐nm scale nanopatterns that are remarkably well aligned along the atomic edge of 2D flakes. Self‐assembled nanodomains are elucidated based on alternation of the wetting layer of the BCP film in the presence of intermediate 2D flakes. This novel approach highlights the synergistic integration of bottom‐up nanofabrication.